Oxidative Stress and Overview of Pediatric Disease Biomarkers - Ayaz, Ahmet (GEORG THIEME VERLAG KG, 2015)
Free radicals are small molecules enabled to react with other biological molecules. The antioxidant system in metabolism is responsible for balancing antioxidant levels and the amount of free radicals. Excessive free radicals production will result in oxidative stress. A certain amount of reactive oxygen species are required to maintain normal physiological activity. However, elevated oxidative stress levels will damage molecules and produce enzymatic malfunction. Several pediatric diseases are associated with increased oxidative stress. A biomarker is a specific molecule that acts as an indicator for a specific condition. There are some oxidative stress biomarkers currently in uses and further analysis of their application is required. Protein molecules may serve as potential biomarker according to proteomics analysis.
Keywords: oxidative stress; biomarker; proteomics; pediatric diseases; Pediatrics